Flash flood susceptibility mapping of sungai pinang catchment using frequency ratio - Azlan Saleh; Ali Yuzir (Penerbit Universiti Kebangsaan Malaysia, 2022)
Flash flood are natural disasters that frequently occur in Malaysia especially in urban areas. Due to this, the development of flash flood susceptibility mapping one of the tools used to aid the local authority in reducing and managing the flash flood impact. Frequency Ratio (FR) is a popular method in predictive modeling because of its capabilities to determine the critical conditioning factor of flash flood. The aim of this research was to compare the standalone FR with Ensemble FR-AHP. This ensemble method uses pair-wise comparison method between Frequency Ratio and Analytical Hierarchy Process (AHP). For this research, ten conditioning factors were selected which were slope, aspect, curvature, Topographic Wetness Index (TWI), Stream Power Index (SPI), Normalized Difference Vegetation Index (NDVI), distance from river, rainfall, elevation, and land use/land cover (LULC). The flash flood inventory was obtained from local authorities where the flash flood occurred in Penang, Malaysia on November 2017. 70% of 110 flooded locations were used as training dataset to assess the spatial distribution of flooding whereas the remaining 30% flooded locations were used as validation dataset. Based on the results, the prediction rate of FR-AHP method is slightly better accuracy compared to FR method which 88.33% (FR-AHP) and 85.62% (FR). The output of this research is crucial to assist local authority in land use planning and drainage system of the study area.